Moisture adsorption in water caltrop (Trapa bispinosaRoxb.) pericarps: Thermodynamic properties and glass transition. (25th May 2020) - Cheng, Xinfeng; Zhang, Min; Adhikari, Benu
Abstract: Moisture sorption isotherms of water caltrop pericarp (WCP) powders were determined at 20, 30, and 40°C over water activity ( A w ) range of 0.11 and 0.97. The adsorption isotherms decreased with the increase of temperature and exhibited Type II BET adsorption characteristics. The monolayer moisture content values calculated by the Guggenheim–Anderson–de Bor equation were found to be 0.0561, 0.0509, and 0.0409 g/g solids at 20, 30, and 40°C, respectively. The values of net isosteric heat of adsorption and differential entropy decreased from 26.094 to 0.250 kJ/mol, 76.665 to 0.358 J mol −1 K −1 with water content varying from 0.30 to 0.07 g/g solids, respectively. The isokinetic theory showed that the water adsorption process of WCP powders was governed by enthalpy. The values of specific surface area available for adsorption at 20, 30, and 40°C were 198.95, 180.40, and 145.11 m 2 /g, respectively. The spreading pressure increased with the increase of A w values at a fixed temperature and decreased when temperature rising at a given A w level. The effective pore size for WCP powders increased with the increment of water content and temperature, ranging from 1.648 to 21.761 nm. The glass transition temperature ( T g ) of WCP powders was examined by differential scanning calorimetry and its values decreased from 72.34 to 2.42°C as water content ranged from 0.0499 to 0.352 g/g solids. The result showed that WCP powders remained stable at 30°C when the moisture content was lower than 0.149 g/g solids. Practical applications: Water caltrop ( Trapa bispinosa Roxb) has been widely cultivated in China and other Southeast Asia because of its medical functions and delicious taste. The micronized water caltrop pericarp (WCP) is an excellent source of dietary fiber and phenolics and has been applied in various food and nonfood sectors. The objectives of this work were to evaluate the thermodynamic properties of water adsorption isotherms of WCP powders. In addition, a state diagram was established based on the water activity concept and glass transition theory. The results documented in this study will help design the energy process for producing WCP powders and predicting storage stability. Abstract :